Antibodies against nodo-paranodal proteins are not present in genetic neuropathies. (28th July 2020) - Martín-Aguilar, Lorena; Pascual-Goñi, Elba; Lleixà, Cinta; Frasquet, Marina; Argente, Herminia; Cano-Abascal, Angel; Diaz-Manera, Jordi; Cortés-Vicente, Elena; Pelayo-Negro, Ana Lara; Sevilla, Teresa; Rojas-García, Ricard; Querol, Luis
Abstract : Objective: To study the presence of nodal and paranodal immunoglobulin M (IgM) and immunoglobulin G (IgG) antibodies in patients with genetic neuropathies. Methods: A total of 108 patients with genetic neuropathies from 3 different centers were included. The presence of IgG and IgM antibodies against neurofascin-155 (NF155), nodal neurofascin (NF186 and NF140), and contactin-1 (CNTN1) were investigated with a cell-based assay (CBA) using immunocytochemistry in transfected HEK293 cells. Sera with positive or uncertain results were further tested by ELISA and immunohistochemistry in pig teased-nerve fibers. Results: Six patients with Charcot-Marie-Tooth disease (CMT) had an uncertain staining pattern for IgM against nodal neurofascin that was not confirmed by ELISA. Two patients with CMT had an uncertain staining pattern for IgG against nodal neurofascin that was not confirmed by ELISA or immunohistochemistry. One patient with CMT with a confirmed GJB1 mutation tested positive for IgG against NF155 by CBA and ELISA (1/900), but was not confirmed by immunohistochemistry and was ultimately classified as negative. Conclusions: Antibodies against nodal or paranodal antigens were not detected in our cohort of patients with CMT, as previously reported. Some patients may falsely test positive for any of the techniques; confirmatory techniques should be incorporated into the routine testing.